Sustainable collaboration between public libraries and school resource centers: advancing digital Information literacy in the digital age/ Haizatul Afni Bakhtiar, Roziya Abu and Norshila Shaifuddin - Bakhtiar, Haizatul Afni; Abu, Roziya; Shaifuddin, Norshila (Faculty of Information Management, 2024)
This study explores the essential role of digital information literacy (DIL) in Malaysian schools and its integration within the context of sustainable development and educational collaboration. As Malaysia continues to advance its sustainability agenda, underscored by the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), this research investigates the effectiveness of DIL initiatives in enhancing educational outcomes. The study highlights the evolving landscape of library and media services, with a focus on the collaboration be-tween state public libraries and school resource centers. Data collected through qualitative methods, including interviews with librarians and key educational stakeholders, reveal that while many educators are familiar with basic digital tools like Google, there is a notable gap in advanced internet search techniques and critical information evaluation skills. The findings underscore the necessity for com-prehensive training programs that equip teachers with robust digital literacy skills before they can effectively impart these skills to students. Additionally, the research emphasizes the need for collaborative efforts among educators to diversify information search methods and enhance the overall effectiveness of DIL programs. This study aims to foster a more inclusive and effective approach to digital literacy, ultimately contributing to Malaysia's broader educational and sustainability goals.